Tigers in trouble : financial governance, liberalisation and crises in East Asia - Jomo K. S. (Hong Kong Cape Town Dhaka, Bangladesh London ; New York New York: Hong Kong University Press ;: IPSR Books ;: University Press ;: Zed Books ;: Distributed in the USA exclusively by St. Martin's Press, 1998)
"This book provides a cogent critique of the nature of Southeast Asian capitalism. It argues powerfully that the crises are due not to excessive regulation, but to too much financial liberalisation and a consequent undermining of monetary and fiscal governance. While recognising some macroeconomic problems and abuses of state intervention in the region, the book also highlights the nature and implications of IMF and domestic policy responses which exacerbated the crises." "The analysis contained in this book raises profound questions which resonate way beyond the Asian region itself. They relate to the appropriate role of the state, the policies of the IMF and the viability of the deregulated free market capitalist model which these and other Third World countries have been encouraged to pursue."--Jacket.
Introduction : Financial governance, liberalisation and crises in East Asia / Jomo K.S. -- The East Asian financial crisis : back to the future / Yilmaz Akyiiz -- East Asia is not Mexico : the difference between balance of payments crises and debt deflation / J.A. Kregel -- Hubris, hysteria, hope : the political economy of crisis and response in Southeast Asia / C.P. Chandrasekhar and Jayati Ghosh -- Taming the tigers : the IMF and the Asian crisis / Nicola Bullard, Walden Bello and Kamal Malhotra -- Thailand : causes, conduct, consequences / Laurids S. Lauridsen -- Indonesia : reaping the market / Manuel F. Montes and Muhammad Ali Abdusalamov -- Malaysia : from miracle to debacle / Jomo K.S. -- The Philippines and the East Asian economic turmoil / Joseph Y. Lim -- South Korea : the misunderstood crisis / Chang Ha-Joon -- Afterword : the East Asian and other financial crises -- causes, responses and prevention / G.K. Helleiner.
A collection 10 essays by the editor and other authors.
Includes bibliographical references (p. [239]-247) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: International Monetary Fund; International finance; Financial crises -- -- East Asia; Monetary policy -- -- East Asia; Capital market -- -- East Asia; Financiële crises; Financiële politiek; IMF; Geldpolitik; Wirtschaftskrise; Kapitalmarkt; Ostasien; Südostasien.